2012
DOI: 10.3389/fphys.2012.00438
|View full text |Cite
|
Sign up to set email alerts
|

Protein aggregation profile of the human kinome

Abstract: Protein aggregation into amyloid fibrils is associated with the onset of an increasing number of human disorders, including Alzheimer's disease, diabetes, and some types of cancer. The ability to form toxic amyloids appears to be a property of most polypeptides. Accordingly, it has been proposed that reducing aggregation and its effect in cell fitness is a driving force in the evolution of proteins sequences. This control of protein solubility should be especially important for regulatory hubs in biological ne… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 49 publications
(74 reference statements)
1
8
0
Order By: Relevance
“…Even when the native protein structure is perturbed and these segments become solvent exposed, they still tend to promote local structural order by self‐associating to nucleate and propagate cross‐β steric zipper motifs that may eventually lead to highly ordered fibrillary structures. Several of these order promoting properties of the APRs have been also reported in earlier studies …”
Section: Discussionsupporting
confidence: 78%
See 3 more Smart Citations
“…Even when the native protein structure is perturbed and these segments become solvent exposed, they still tend to promote local structural order by self‐associating to nucleate and propagate cross‐β steric zipper motifs that may eventually lead to highly ordered fibrillary structures. Several of these order promoting properties of the APRs have been also reported in earlier studies …”
Section: Discussionsupporting
confidence: 78%
“…Protein aggregation often results in protein inactivation . Recent surveys of monomeric protein structures suggested that APRs are found close to enzyme catalytic sites . Here, the distribution of TANGO and WALTZ predicted APRs around the active and binding sites in 587 protein chains was analysed by calculating the distances between active or binding site residues and the residues found in the APRs.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The composition of different protein sequences in our dataset has been deduced using various parameters such as hydropathy (GRAVY), unfoldability, aggregation propensity, instability, charge and disorder by applying bioinformatics based prediction tools such as ProtParam [24] , FoldIndex [25] , IUPRED [26] , [27] and Aggrescan [28] . These tools have proved valuable in characterizing the functions of numerous novel proteins in the past [45] [48] .…”
Section: Discussionmentioning
confidence: 99%